Why and How Bioethics Must Turn toward Justice: A Modest Proposal - Reardon, Jenny (The Hastings Center report, 2020)
In this essay, I argue that to create a genomics that offers more gifts than weights, central attention must be paid to questions of justice. This will require expanding bioethical imaginations so that they grasp and can respond to questions of structural inequity. It will necessitate building novel coalitions and collaborations that turn the attention of bioethical governance away from narrow individual questions such as, “Do I consent?” and toward the broader collective question, is this just? What kind of lives and collectivities are made possible? What rights and principles should govern them? The essay ends with one example of this novel coalition building arising from the Science and Justice Research Center at the University of California, Santa Cruz. It draws lessons from this effort to build new alliances that bridge the social sciences and natural sciences, arts and engineering, to create new kinds of training and thinking that create a genomics that more adequately responds to fundamental questions of justice.